Lattice Boltzmann simulation of TiO2-water nanofluid in a curved boundary domain at high Rayleigh numbers. (30th May 2018) - Abadshapoori, M. Hosseini; Saidi, M.H.
Highlights: Simulation of high Rayleigh number natural convection. Two-component simulation of nanofluids in natural convection. Including nanoparticle size effect on the Nusselt number. Studying the effect of boundary conditions on the nanoparticle. Abstract: In this paper, a two-component Lattice Boltzmann Method (LBM) has been utilized to simulate the natural convection of TiO2 -water nanofluid in a curved geometry. The main purpose of this research is to study the effect of nanoparticle size and also boundary conditions on the thermal characteristics of the nanofluid. Furthermore, the effect of Rayleigh number (Ra) and volume fraction of nanoparticles ( ϕ ) on the average Nusselt number (Nuave ) have been investigated. Two different thermal boundary conditions, namely adiabatic and constant temperature, have been considered in the current work for the curved boundaries. The Rayleigh number varies from 10 3 to 10 9 . Four different sizes, namely 10, 25, 65 and 90 nm, have been chosen for nanoparticles. Results show that the augmentation of nanoparticle size has a deteriorating effect on the effectiveness of nanoparticles while increasing Ra number and ϕ improves Nusselt number (Nu). It is also shown that the boundary conditions change the enhanced Nusselt number (Nu*). The effect is shown to be due to the variation of nanoparticles motion dictated by the boundary conditions. Furthermore, results reveal that increasing volume fraction increases viscosity which at higher values of ϕ might reduce Nu*.